The secrets we keep : a novel - Lillard, Amy (Crooked Lane, 2025)
"Back to active duty after an administrative leave of absence for the use of deadly force, the last thing Detective Nathan Fisher wants to do is return to the conservative Amish community he left behind, but when his father passes, he has no choice. Hoping to clear his head and perhaps mend fences with his family, he returns to his small Mississippi hometown despite not being welcome. What was supposed to be a quick visit turns into a prolonged stay when his former love pleads for his help. Rachel Hostetler's world is turned upside down when she finds her brother's body hanging in her family's barn. Rachel is sure her brother Albie did not kill himself, but neither her father nor the police are willing to listen. When she spots Nate, her ex, now a detective in Oklahoma, back in Cedar Creek, she knows he is the answer to her problem and begs him to intercede. As Nate and Rachel come to terms with their shared history, despite knowing nothing can come of the longing they have for each other, the pair must look into Albie's death as suspects stack up. The truth is out there, but can they find it before Nate has to return to his real life and face the shooting that has him so desperately searching for peace?" --